A Coupled 1D-2D Hydrodynamic Model for Urban Flood Inundation - Yuyan Fan; Tianqi Ao; Haijun Yu; Guoru Huang; Xiaodong Li (Advances in Meteorology)
Hydrodynamic models were commonly used for flood risk management in urban area. This paper presents initial efforts in developing an urban flood inundation model by coupling a one-dimensional (1D) model with a two-dimensional (2D) model to overcome the drawbacks of each individual modelling approach, and an additional module is used to simulate the rainfall-runoff process in study areas. For the 1D model, the finite difference method is used to discretize the Saint-Venant equations. An implicit dual time-stepping method (DTS) is then applied to a 2D finite volume model for an inundation simulation to improve computational efficiency. A total of four test cases are applied to validate the proposed model; its performance is demonstrated by a comparison with an explicit scheme and previously published results (an extensive physical experiment benchmark case, a vertical linking example, and two real drainage cases with actual topography). Results demonstrate that the proposed model is accurate and efficient in simulating urban floods for practical applications.